RESTORATIVE JUSTICE UNTUK PERADILAN DI INDONESIA (Perspektif Yuridis Filosofis dalam Penegakan Hukum In Concreto) - KuatPuji Prayitno (Jurnal Dinamika Hukum, 2012)
Restorative justice is a philosophy, a process, an idea, a theory and an intervention, that emphasizes repairing the harm caused or revealed by criminal behaviour. This process is in stark contrast to the established way of addressing crime which are seen as offences committed against the State. Restorative justice finds its footing in the basic philosophy of the four precepts of Pancasila, namely prioritizing deliberation in decision making. Purpose of the settlement with the Victim Offender Mediation is to "humanize" the justice system, that fairness is able to answer what the actual needs of victims, offenders and communities.  Key words: Restorative justice, victim offender mediation, repairing the harm